Synthesis of isobemisiose, neosartose, and fischerose: three α-1, 6-linked trehalose-based oligosaccharides identified from Neosartorya fischeri. Issue 38 (12th June 2020) - Kuenstner, E. J.; Palumbo, E. A.; Levine, J.; Snyder, N. L.
Abstract : The first concise and scalable chemical synthesis of three complex α-1, 6-linked trehalose-based oligosaccharides, isobemisiose, neosartose, and fischerose, are reported for the first time. Abstract : Three complex α-1, 6-linked trehalose-based oligosaccharides with unique preservation properties, isobemisiose, neosartose, and fischerose, were recently identified from the extreme stress-tolerant ascospores of Neosartorya fischeri. Herein, we report the first concise, scalable, and iterative chemical synthesis of these oligosaccharides from a differentially protected thioglycoside donor and a selectively protected, asymmetric trehalose acceptor. This work constitutes an improved synthesis of isobemisiose, and is also the first reported synthesis of neosartose, a tetrasaccharide, and fischerose, a pentasaccharide, in good yield. Importantly, in-depth studies of biological function are enabled by this synthetic platform.